Tingkat Kesiapan dan Tantangan Calon Guru Sekolah Dasar dalam Menyusun Modul Ajar Berbasis Kurikulum Merdeka - Yanuar, Melinda; Aida Sari, Fitri (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Mulawarman, 2025)
The readiness of prospective elementary school teachers in compiling teaching modules for the Independent Curriculum is crucial in elementary school learning. The process of compiling teaching modules is a challenge for prospective elementary school teachers. This study aims to determine the challenges and readiness in compiling teaching modules. The method used is a quantitative descriptive approach with data collection techniques through distributing questionnaires. The subjects of the study consisted of 38 students of the Elementary School Teacher Education Study Program in East Kalimantan. The results of the readiness of prospective elementary school teachers in compiling teaching modules based on the Independent Curriculum are generally at a fairly good level, with the majority of students showing adequate understanding of the steps in compiling teaching modules. The implications of this study indicate the need for adjustments in the teaching approach in higher education, with a focus on strengthening practical skills through learning methods such as project-based learning and mentoring